The influence of knowledge and attitudes about HIV/AIDS on adolescent sexual behaviour during the COVID-19 pandemic in Jayapura, Papua - Simanungkalit, Bona; Maria, Dely; Sinaga, Carmen (International Journal Of Community Medicine And Public Health, 2025)
Background: The prevalence of HIV/AIDS in Indonesia reached more than 500,000 cases. Cases of 36,997 in Papua province, is in the top three. This condition is especially in teenagers, it has an impact on the quality of future human resources. Free sex behavior causes extramarital relationships in teenagers so the transmission of this is faster. The purpose of the study was to determine the effect of teenagers knowledge and attitudes about HIV/AIDS on teenagers sexual behavior. Methods: The design that used cross sectional. The population is all students of SMAN 4 Jayapura-Papua. The sampling method is purposive sampling. Inclusion criteria: Students of SMAN 4 Jayapura-Papua, Willing to be respondents by filling in and agreeing and signing the informed consent. Exclusion criteria: not willing to be respondents. Data collection was conducted for 2 months (June - July). Early research was conducted at SMAN 4 Jayapura, and before the research was conducted, validity and reliability tests were conducted on 20 respondents. Statistical tool (software) used to analyse the data with SPSS. Multivariate and logistic regression analyzed, statistical tests using ANOVA with a significance level of p <0.05. Results: From 539, 58.6% of female respondents, 50.1% protestant, 43% father's job is self- employed, 54.2% mother is unemployed, father and mother's education are above high school, good communication in family, 78.7% less than 3 siblings, 64.6% source of information from the media, knowledge about HIV/AIDS is deficient (59.9%), attitude is deficient (58.6%) and sexual behavior of teenagers is 97% deficient. Relationship between knowledge and behavior p=0.964, Odds Ratio (OR)=1.169. Multivariate modeling of the influence of knowledge and attitude on sexual behavior OR=0.773 and 0.518. Conclusions: The influence of knowledge and attitude about HIV/AIDS on teenagers sexual behavior during the Covid-19 pandemic, was not significant and knowledge dominantly influence on sexual behavior.